Development Of Working Electrode Modified By Iron Oxide Nanoparticles For Glucose Biosensor Applications - Mohamad Nor, Noorhashimah (2019)
Glucose biosensor that is capable to provide wide linearity of detection, high sensitivity, and low limit of detection is important in clinical diagnosis. This has motivated the research into development of a better glucose biosensor. In this study, iron oxide nanoparticles (IONPs) were synthesized using the precipitation method and surface functionalized with varying citric acid (CA) concentration (0.10, 0.25, 0.50, and 0.70 g/ml) to produce stable colloidal IONPs in water. The effect of varying CA concentration on the crystallinity and morphology, of the IONPs–CA in water were studied using X-ray diffraction (XRD) and transmission electron microscope (TEM). From the XRD patterns, high crystallinity of spinel cubic lattice of maghemite (γ- Fe2O3) was obtained, while observation using transmission electron microscopy (TEM) showed particle size was in the range of 17–22 nm. The optimum CA concentration to functionalize IONPs–CA forming stable colloidal IONPs in water and exhibited excellent electrochemical performance was 0.25 g/ml. The stable colloidal IONPs–0.25 CA in water was then applied for fabrication of enzymatic and nonenzymatic glucose biosensor by modification of working electrode using drop casting method. In enzymatic glucose biosensor, the indium tin oxide (ITO) electrode and screen printed carbon electrode (SPCE) were modified with IONPs–0.25 CA, glucose oxidase (GOx) enzymes and Nafion layer. As for non-enzymatic glucose biosensor, the SPCE electrode was modified with IONPs–0.25 CA and Nafion layer. The optimization parameters of enzymatic and non-enzymatic glucose biosensors performance were conducted, such as effect of IONPs concentration, effect of GOx enzyme loading concentration, effect of working potential, effect of buffer solution pH and effect of operating temperature. The sensing performance of the developed enzymatic and non-enzymatic glucose biosensor exhibit excellent glucose detection performance with sensitivity of Nafion/GOx/IONPs–0.25 CA/ITO (941 μAmM-1cm-2 and limit of detection of 0.10 μM), Nafion/GOx/IONPs–0.25 CA/SPCE (164 μAmM- 1cm-2 and limit of detection of 14 μM), and 5Nafion/IONPs–0.25 CA/SPCE (2802 μAmM-1cm-2 and limit of detection 0.60 μM). The wide linearity of detection, high sensitivity and low limit of detection of enzymatic and non-enzymatic glucose biosensors were successfully developed based on modification of working electrode with IONPs–0.25 C